The Impact of Cigarette Smoking on the Oral Mucosa - Adamczyk, Adrianna; Gałuszka, Maja; Gałuszka, Aleksandra; Krycia, Kamila; Mazur, Karolina; Różycka, Karolina; Mulawa, Magdalena; Piaszczyńska, Emilia; Matacz, Dominika; Drabik, Sandra (Journal of Education, Health and Sport, 2026)
Introduction. Tobacco smoking is the most common addiction worldwide. It is estimated that there are currently around 1.2 billion people addicted to this product globally (Reibel, 2005). The situation in Poland is not more optimistic - approximately 27–28% of adult Poles declare this habit (TNS Polska, n.d.). Each year, tobacco is responsible for the deaths of over 7 million people worldwide (World Health Organization, n.d.). Tobacco smoke contains approximately 4,000 chemical compounds, many of which are carcinogenic substances (Piekoszowski & Florek, 2001; Rudzinski & Banach, 2008). Aim. The aim of this study is to present the harmful effects of tobacco smoke on the condition of the oral mucosa and to discuss the most common pathological changes associated with exposure to tobacco smoke. Material and methods. The research material consisted of scientific publications concerning the impact of cigarette smoking on the oral mucosa. The literature review was conducted based on the PubMed and Google Scholar databases. Publications in both Polish and English, published between 1987 and 2023, were included.